2018
DOI: 10.1038/s41598-018-32420-3
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Changes Caused by Inflammation and Oxidative Stress in Diet-Induced-Obese Mouse following Experimental Lung Injury

Abstract: Obesity has been identified as a risk factor for adverse outcomes of various diseases. However, information regarding the difference between the response of obese and normal subjects to pulmonary inflammation is limited. Mice were fed with the control or high-fat diet to establish the lean and diet-induced obese (DIO) mice. Escherichia coli was intranasally instilled to reproduce non-fatal acute pneumonia model. After infection, serum samples and lung tissues were obtained at 0, 12, 24, and 72 h. DIO mice exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…Mice from Lean-E. coli and DIO-E. coli groups underwent intranasal instillation with 40 μL of a suspension containing ~10 9 CFU of E. coli. Mice from Lean-PBS and DIO-PBS groups were given the same dose of PBS 4,5 . Two mice which died within 6 h of intranasal instillation were removed.…”
Section: Intranasal Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice from Lean-E. coli and DIO-E. coli groups underwent intranasal instillation with 40 μL of a suspension containing ~10 9 CFU of E. coli. Mice from Lean-PBS and DIO-PBS groups were given the same dose of PBS 4,5 . Two mice which died within 6 h of intranasal instillation were removed.…”
Section: Intranasal Infectionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that obesity played a protective part in pneumonia 4,5 . Preliminary study of Gu reported that obesity could alleviate oxidative damage and inflammation of mice spleen under the condition of non-fatal acute pneumonia induced by Escherichia coli 6 .…”
mentioning
confidence: 99%
“…Obesity is growing rapidly around the world, and the diseases associated with obesity have been highlighted in recent years, especially pulmonary disease. Recently, studies suggested that obesity plays a beneficial role in E. coli pneumonia, manifesting that clinically significant changes in pulmonary inflammatory response may be associated with immune status in obesity [4,5]. The spleen is the center of cellular immunity and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Fascinatingly, Wan et al [4] have reported that the obese mice exhibited more lymphocytes in the bronchoalveolar lavage fluid and milder lung injury than normal mice under the case of nonfatal pneumonia caused by E. coli, suggesting that obesity can improve immune responses against bacterial pneumonia. The DIO mice also presented a delayed pulmonary inflammatory response and oxidative stress in pneumonia induced by E. coli infection [5]. In addition, the previous study found that the changes of hepatic histopathological damage, oxidative damage, and higher levels of cytokines (TNF-α, IL-6, and resistin) showed to be less severe in the DIO mice than in the normal mice following E. coli pneumonia [6].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation